1983
DOI: 10.3109/00016488309132875
|View full text |Cite
|
Sign up to set email alerts
|

Pertlymph Oxygenation in Sudden and Progressive Sénsorineural Hearing Loss

Abstract: The perilymphatic oxygen tension of the vestibular perilymph of 34 patients with different inner ear losses were measured with the polarographic method before and after inhalation with carbogen. Two patterns of disturbed perilymphatic oxygenation were observed: 1) Characterized by low initial values of perilymphatic oxygenation and normal response to carbogen inhalation was present in sudden deafness and sudden cochleovestibular loss of inner ear function. 2) Characterized by normal initial values of perilymph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
1
5

Year Published

1984
1984
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 3 publications
1
31
1
5
Order By: Relevance
“…Moreover, arterial hypertension may cause ionic changes in cell potentials, resulting in hearing loss. 58,59 It is possible that hypertension could, through such factors, cause hearing impairment, and consequently, it would be expected that workers exposed to high noise levels and having hypertension would be more prone to hearing impairment and hearing loss. 59 The occurrence of hearing impairment in our exposed population was not associated with hypertension.…”
mentioning
confidence: 99%
“…Moreover, arterial hypertension may cause ionic changes in cell potentials, resulting in hearing loss. 58,59 It is possible that hypertension could, through such factors, cause hearing impairment, and consequently, it would be expected that workers exposed to high noise levels and having hypertension would be more prone to hearing impairment and hearing loss. 59 The occurrence of hearing impairment in our exposed population was not associated with hypertension.…”
mentioning
confidence: 99%
“…[11] It was found that perilymphatic oxygen tension decreased in patients with SSNHL, while under hyperbaric conditions, oxygen tension in the perilymphatic fluid increased by 450% [12,13] . These days, HBO therapy is used as primary or as salvage therapy for sudden haring loss [14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension, the most common vascular disorder, may facilitate structural changes in the heart and blood vessels. High pressure in the vascular system may cause inner ear hemorrhage, which is supplied by the anterior inferior cerebellar artery, which supports the inner ear artery and is divided into cochlear artery and anterior vestibular artery [4], which may cause progressive or sudden hearing loss [3,5]. This circulatory system pathology may directly affect hearing in a number of ways.…”
Section: Introductionmentioning
confidence: 99%